Strain Localization in Thin Films of Bi(Fe,Mn)O(3) Due to the Formation of Stepped Mn(4+)-Rich Antiphase Boundaries - MacLaren, I (Nanoscale Res Lett, 2015)
The atomic structure and chemistry of thin films of Bi(Fe,Mn)O(3) (BFMO) films with a target composition of Bi(2)FeMnO(6) on SrTiO(3) are studied using scanning transmission electron microscopy imaging and electron energy loss spectroscopy. It is shown that Mn(4+)-rich antiphase boundaries are locally nucleated right at the film substrate and then form stepped structures that are approximately pyramidal in three dimensions. These have the effect of confining the material below the pyramids in a highly strained state with an out-of-plane lattice parameter close to 4.1 Å. Outside the area enclosed by the antiphase boundaries, the out-of-plane lattice parameter is much closer to bulk values for BFMO. This suggests that to improve the crystallographic perfection of the films whilst retaining the strain state through as much of the film as possible, ways need to be found to prevent nucleation of the antiphase boundaries. Since the antiphase boundaries seem to form from the interaction of Mn with the Ti in the substrate, one route to perform this would be to grow a thin buffer layer of pure BiFeO(3) on the SrTiO(3) substrate to minimise any Mn-Ti interactions.